The problems of the principle of legal security - Maslovskaya, Tatiana S.; Mathieu, Bertrand (Journal of the Belarusian State University. Law, 2020)
The article provides a general overview of certain aspects of the content of the principle of legal security from the point of view of Belarusian and French law. Close attention is paid to the quality of legal norms and the predictability of legal regulation. The conclusion is made about the role of legal security in modern conditions.
Keywords: legal security; predictability of legal regulation; quality of law; French Republic; Republic of Belarus